2022
DOI: 10.1007/s13197-022-05507-z
|View full text |Cite
|
Sign up to set email alerts
|

Blends of palm kernel oil, soybean oil and palm stearin as an alternative to milk fat for frozen dessert application

Abstract: In this study, the ternary blends of palm kernel oil (PKO), soybean oil (SBO) and two types of palm stearin (PS) (PS33 and PS38) were systematically prepared and evaluated for their application as an alternative to milk fat in frozen dessert. The physicochemical characteristics namely fatty acids constituent, triacylglycerols (TAGs) composition, melting behavior, solid fat content (SFC) and microstructure were studied. All ternary blends of PKO/SBO/PS33 and PKO/SBO/PS38 had comparable microstructure to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The United States Department of Agriculture (USDA) has reported that plant oils are 2−5 times cheaper than milk fat (i.e., it costs $1000− $2000 USD per metric ton for edible oils versus $4000−$5000 USD per metric ton for butterfat). 55 Additionally, the demand for dairy-free foods, including ice cream, is increasing daily. Hence, food manufacturers are looking for suitable alternatives to milk fat, and the use of plant oils is increasing.…”
Section: Plant-based Dairy Alternatives For Ice Cream Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“…The United States Department of Agriculture (USDA) has reported that plant oils are 2−5 times cheaper than milk fat (i.e., it costs $1000− $2000 USD per metric ton for edible oils versus $4000−$5000 USD per metric ton for butterfat). 55 Additionally, the demand for dairy-free foods, including ice cream, is increasing daily. Hence, food manufacturers are looking for suitable alternatives to milk fat, and the use of plant oils is increasing.…”
Section: Plant-based Dairy Alternatives For Ice Cream Applicationmentioning
confidence: 99%
“…It has a melting range of 26−28 °C, making it a semi-solid fat. 55 PKO is high in lauric and myristic acids and has a sharp melting profile. Thus, it is suitable for confectioneries and other food applications including fat spreads, margarine, cocoa butter substitutes, shallow frying, and filling creams.…”
Section: Plant-based Dairy Alternatives For Ice Cream Applicationmentioning
confidence: 99%
See 3 more Smart Citations